Formação e atuação profissional: um estudo comparativo com egressos do curso técnico em lazer do IFMA e de curso de graduação em lazer e turismo da EACH/USP - Carla Augusta Nogueira Lima e Santos (2018)
The vocational training possibilities, specifically to perform in the field of leisure, are presented under different modalities in Brazil: training program, extension course, technical, undergraduate and postgraduate courses lato e stricto sensu. The growth of these training programs is linked to the expansion of the entertainment industry and the recognition of leisure as a fundamental right in order to achieve an optimal level of quality of life. The present study opted to study and compare two of these modalities: the Leisure Technical Course, offered by Federal Institute of Maranhão, and the undergraduate course in Leisure and Tourism, offered by School of Arts, Sciences and Humanities of the University of São Paulo. The goal was to analyse the vocational training profile of these institutions and identify the further insertion of its egresses in the labour market, identifying the sectors of the national economy to which they get linked to, and also the role they perform. The strategy chosen for data collection combined bibliographic research, documentation and fieldwork. The documentation research focused on the analysis of the pedagogical projects of the courses, and the field research was carried out with 89 graduates through an online questionnaire. After analyzing the Pedagogical Projects of the courses, it was possible to conclude that both were created to meet the demands of the labor market, since they understand leisure as a promising and profitable field, which requires certain specific workers. In both programs, it was identified a concern in educating individuals beyond straght-forward productivity, but also recognizing the need for a broader sense education, that also values the search for individual autonomy and a critical view of the social, economic, political and cultural context. From the respondents' answers to the questionnaire, it was possible to identify that: 58.42% of the former students of both courses are not working in the area in which they were educated for. The main reasons for this were the lack of opportunity and income below expecations. In addition, 41.57% of those who are inserted in the leisure sector are working for the private sector and have a employment agreement under the CLT (Brazilian Labor Regulation for formal employment and its mandatory benefits) regulation. The egresses of the technical course work for a community center for the elderly, as the graduates in Leisure and Tourism work in different places, such as Agencies and Operators of Leisure and Tourism; hotels, Events Company and Employers - SESC. The leisure technicians work in coordination, elaboration and execution of leisure activities, as the graduates in leisure and tourism, in addition to these, still assume functions such as consulting, business management and developing activities in the field of tourism. Although the pedagogical projects of the institutions under analysis have similarities regarding the definitions of professional standards and the possibilities of social intervention, I have identified that the main differences are related to the length of the courses, which reflects in the study depth of the subjects, and also in the different economic background, social reality and cultural complexities between São Paulo and Maranhão, which directly influence the employment opportunities and continuing education of graduates.